A novel Drosophila alkaline phosphatase specific to the ellipsoid body of the adult brain and the lower Malpighian (renal) tubule. - Yang, M.Y.; Wang, Z.; MacPherson, M.; Dow, J.A.; Kaiser, K. (Genetics, 2000)
Two independent Drosophila melanogaster P(GAL4) enhancer-trap lines revealed identical GAL4-directed expression patterns in the ellipsoid body of the brain and in the Malpighian (renal) tubules in the abdomen. Both P-element insertions mapped to the same chromosomal site (100B2). The genomic locus, as characterized by plasmid rescue of flanking DNA, restriction mapping, and DNA sequencing, revealed the two P(GAL4) elements to be inserted in opposite orientations, only 46 bp apart. Three genes flanking the insertions have been identified. Calcineurin A1 (previously mapped to 21E-F) lies to one side, and two very closely linked genes lie to the other. The nearer encodes Aph-4, the first Drosophila alkaline phosphatase gene to be identified; the more distant gene [l(3)96601] is novel, with a head-elevated expression, and with distant similarity to transcription regulatory elements. Both in situ hybridization with Aph-4 probes and direct histochemical determination of alkaline phosphatase activity precisely matches the enhancer-trap pattern reported by the original lines. Although the P-element insertions are not recessive lethals, they display tubule phenotypes in both heterozygotes and homozygotes. Rates of fluid secretion in tubules from c507 homozygotes are reduced, both basally, and after stimulation by CAP(2b), cAMP, or Drosophila leucokinin. The P-element insertions also disrupt the expression of Aph-4, causing misexpression in the tubule main segment. This disruption extends to tubule pigmentation, with c507 homozygotes displaying white-like transparent main segments. These results suggest that Aph-4, while possessing a very narrow range of expression, nonetheless plays an important role in epithelial function.